Transcriptomic signatures reveal immune dysregulation in human diabetic and idiopathic gastroparesis - Madhusudan Grover; Simon J. Gibbons; Asha A. Nair; Cheryl E. Bernard; Adeel S. Zubair; Seth T. Eisenman; Laura A. Wilson; Laura Miriel; Pankaj J. Pasricha; Henry P. Parkman; Irene Sarosiek; Richard W. McCallum; et al. (BMC, 2018)
Abstract Background Cellular changes described in human gastroparesis have revealed a role for immune dysregulation, however, a mechanistic understanding of human gastroparesis and the signaling pathways involved are still unclear. Methods Diabetic gastroparetics, diabetic non-gastroparetic controls, idiopathic gastroparetics and non-diabetic non-gastroparetic controls underwent full-thickness gastric body biopsies. Deep RNA sequencing was performed and pathway analysis of differentially expressed transcripts was done using Ingenuity®. A subset of differentially expressed genes in diabetic gastroparesis was validated in a separate cohort using QT-PCR. Results 111 genes were differentially expressed in diabetic gastroparesis and 181 in idiopathic gastroparesis with a log2fold difference of | ≥ 2| and false detection rate (FDR) < 5%. Top canonical pathways in diabetic gastroparesis included genes involved with macrophages, fibroblasts and endothelial cells in rheumatoid arthritis, osteoarthritis pathway and differential regulation of cytokine production in macrophages and T helper cells by IL-17A and IL-17F. Top canonical pathways in idiopathic gastroparesis included genes involved in granulocyte adhesion and diapedesis, agranulocyte adhesion and diapedesis, and role of macrophages, fibroblasts and endothelial cells in rheumatoid arthritis. Sixty-five differentially expressed genes (log2fold difference | ≥ 2|, FDR < 5%) were common in both diabetic and idiopathic gastroparesis with genes in the top 5 canonical pathways associated with immune signaling. 4/5 highly differentially expressed genes (SGK1, APOLD1, CXCR4, CXCL2, and FOS) in diabetic gastroparesis were validated in a separate cohort of patients using RT-PCR. Immune profile analysis revealed that genes associated with M1 (pro inflammatory) macrophages were enriched in tissues from idiopathic gastroparesis tissues compared to controls (p < 0.05). Conclusions Diabetic and idiopathic gastroparesis have both unique and overlapping transcriptomic signatures. Innate immune signaling likely plays a central role in pathogenesis of human gastroparesis.